Using routine data to examine factors associated with stillbirth in three tertiary maternity facilities in Kabul, Afghanistan - Zainab Ezadi; Sayed Murtaza Sadat Hofiani; Aliki Christou (Reproductive Health)
Abstract Background Over one-third of the global stillbirth burden occurs in countries affected by conflict or a humanitarian crisis, including Afghanistan. Stillbirth rates in Afghanistan remained high in 2021 at over 26 per 1000 births. Stillbirths have devastating physical, psycho-social and economic impacts on women, families and healthcare providers. Data on the risks and causes of stillbirths are critical to target prevention measures and are currently lacking. This study aimed to use routine health facility data to examine the socio-demographic, maternal, fetal, and obstetric characteristics associated with stillbirth. Methods This was a hospital-based case-control study of births at the maternity units of the three tertiary care referral hospitals in Kabul, Afghanistan between March-September 2021. Cases were defined as stillbirths that occurred at 22 weeks or later in pregnancy while live births occurring after each case were selected as controls. Multivariable logistic regression was used to explore factors associated with stillbirth after performing multiple imputation to impute missing data for independent variables. Results A total of 497 cases (stillbirths) and 1069 controls (live births) were included in the analysis. Factors independently associated with stillbirth while adjusting for maternal age and baby’s sex were: being referred from another facility which increased the odds of stillbirth by over three times (aOR 3.24; 95% CI 1.17, 8.85) compared to those who were not referred; being born extremely preterm (< 28 weeks) (aOR 13.98; 95% CI 7.44, 26.27), very preterm (28–31 weeks) (aOR 3.91; 95% CI 2.73, 5.62), and moderate to late preterm (32–36 weeks) (aOR 2.32; 95% CI 1.60, 3.37) compared to term babies; and being small-for-gestational age (aOR 1.70; 95% CI 1.10, 2.64) compared to those that were average size for gestational age. Placental abruption also increased the odds of stillbirth by two times (aOR 2.07; 95% CI 1.37–3.11). Conclusions Improving the detection and management of preterm births, and small-for-gestational age babies through improvements in antenatal care attendance and quality will be important for future stillbirth prevention in Afghanistan. More research is needed to understand referral delays and contributing factors to increased risk among referrals. Strengthening routine data quality for stillbirths is imperative for improved understanding and prevention of stillbirths.